Effect of hyaluronic acid-enriched transfer medium on frozen–thawed embryo transfer outcomes in RIF patients: a single-centre retrospective study - Yan, Qiang; Zhao, Mei; Hao, Fan; Zhao, Ruru; Teng, Xiaoming; He, Bin; Zhu, Chong; Chen, Zhiqin; Li, Kunming (Frontiers in Endocrinology, 2023)
Many patients who undergo assisted reproductive technology (ART) suffer from recurrent implantation failure (RIF). The addition of hyaluronic acid (HA) to the transfer medium is one of several methods to improve pregnancy outcomes. We investigated whether HA could improve the live birth and clinical pregnancy rates of RIF patients. This study included 248 RIF patients, who were divided into two groups: the control (CTL) group (n=137), which received transfer medium without HA, and the HA group (n=111), which received transfer medium with HA. The two groups were compared according to the ART outcome. The primary outcomes were the clinical pregnancy and live birth rates. Secondary outcomes include a positive urine pregnancy test, the implantation, ongoing pregnancy, multiple pregnancy, clinical miscarriage, and ectopic pregnancy rates, foetal or congenital defects, obstetric complications, infant birth weight and any related adverse events. Regarding the primary outcomes, the clinical pregnancy rate was significantly higher in the HA group than in the control group, and there was no significant difference in the live birth rate (LBR) between the HA and control groups. Regarding the secondary outcomes, the implantation, multiple pregnancy and ectopic pregnancy rates were similar between the two groups. Our findings supported the conclusion that HA can improve the clinical pregnancy rate of patients with RIF undergoing FET cycles, but the live birth rate was not significantly improved with the addition of HA to the traditional transfer medium.